We have the next variables
x = speed of the boat in still water
y = speed of the current
(x-y) = Upstream speed
(x+y) = downstream speed
So we have the next equations for the distance
![\begin{gathered} 6\mleft(x-y\mright)=408 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/2zxhf875ch40h981b1u8pboirlaekff2ag.png)
![\begin{gathered} 9(x+y)=882 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/v6f9qxxheey98ecoyio2tuyjopbjextsb7.png)
We simplify each equation
![\begin{gathered} x-y=68 \\ x+y=98 \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/md63eujnk8wi4k0fqb94lzc723agz8t7yg.png)
we sum both equations
![\begin{gathered} 2x=166 \\ x=(166)/(2) \\ x=83 \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/mpr524mtjzohigvlm88ttixyoo5kxvyvx1.png)
Then we calculate the y
![\begin{gathered} y=98-x \\ y=15 \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/i4tfjrhu4ze4roazr9ty9773gkv6zicymu.png)
x = speed of the boat in still water=83 km/hr
y = speed of the current 15 km/hr